Green Attitudes and Behaviours of Western Guests at Green Hotels in Phuket, Thailand - Jantiwan Samati (Prince of Songkla University, 2022)
Thesis (M.B.A., Hospitality and Tourism Management (International program))--Prince of Songkla University, 2021